Allelopathic Effect of the Invasive Ludwigia hexapetala on Growth of Three Macrophyte Species - Thiébaut, Gabrielle; Thouvenot, Lise; Rodríguez-Pérez, Hector (Frontiers in Plant Science, 2018)
The release of allelochemicals by plants can affect the performance of other organisms positively or negatively. We tested the effects of aqueous extracts and leachates derived from the leaves and roots of the invasive water primrose (Ludwigia hexapetala) on one submerged native species – Ceratophyllum demersum, and two exotic species – the submerged Egeria densa and the emergent growth form of Myriophyllum aquaticum. The effect of the aqueous extracts and leachates of L. hexapetala on photosynthetic yield, growth (i.e., relative growth rate, leaf area), root length, and length of the lateral shoots of each species were analyzed in spring and in autumn. In autumn, an allelopathic effect was established on the traits of the three macrophytes species. The root extracts stimulated leaf area and the photosynthetic yield of C. demersum and of E. densa, whereas leaf treatments (leachates and extracts) and root leachate reduced the leaf area of M. aquaticum. The autumnal root leachate of L. hexapetala decreased the relative growth rate of C. demersum, whereas it had no effect on the two others plants. The root extract increased the length of lateral branches of M. aquaticum in autumn, suggesting a positive effect of L. hexapetala on the lateral growth of M. aquaticum. Three main allelochemicals were identified in leaves: quercitrin, prunin, myricitrin. The concentrations of these allelochemicals were greater in the leaf extract taken from L. hexapetala in autumn than in spring, and those found in the leaf leachates for both seasons. This assessment of autumnal allelopathy could help to explain the patterns of plant community succession in invaded areas.